Comparison of fracture patterns between rural and urban populations in a developing country. - Saw, A.; Sallehuddin, A.Y.; Chuah, U.C.; Ismail, M.S.; Yoga, R.; Hossain, M.G. (Stamford Publishing Pte Ltd / Singapore Medical Association, 2010)
The anatomical locations of common fractures differed between the urban and rural populations. A higher rate of upper limb fractures was observed in the rural areas, while femur fractures in the elderly was the main cause of fracture admission in the urban areas. The relatively high rate of hand fractures in the rural areas, especially among children and young adults, may require further investigation.